Gender representation in Indonesian online news (A study on detiknews.com) - Yutanti, Widiya (2013)
We live in a world that is stratified along lines of gender, race, ethnicity, class, age, disability, sexuality and location, and in which privileges, disadvantages and exclusions associated with such categories are unevenly distributed. We also live in a world which is increasingly saturated by media and information and communication technologies (Gill 2007: 7).The proposition above underlines the two elements of gender and the media which, together, have represented a longstanding area of concern for critical media scholars and feminists in the world over the past five decades. Studies of gender in the media show that there is gender imbalance in the way in which the world is represented (Azeharie 1997; Brook & Herbert 2006; Cunningham et.al 2004; Cullity & Younger 2009; de Bruin 2000; Gill 2007; van Zoonen 1994).Gender imbalance occurs in many aspects of media practice, such as inequity in the number of males and females as professionals and decision makers in media organisations, gender differences in media use and consumption and even a disproportion in the representation of the two genders in media content including entertainment, advertisements and news. It is becoming a serious issue because the media have a significant influence on individuals and the culture.Debates on the representation of gender in the news media often relate to various cultural and ideological aspects.Indonesia is an example, where a majority of the society is dominated by the patriarchal value system which consequently results in gender bias in many aspects of life, including news media production. Moreover, there are blatant stereotypes in newsroom cultures where a masculine culture dominates news media production.According to Pierre and Nilsson (2004), there is a dichotomous dimension in journalism between male and female genders; the former are usually concerned with topics and issues covered in hard news while the latter are usually more involved in soft news. Hard news includes issues believed to be important to men because they relate to spheres in which men dominate such as politics, the economy and business. In contrast, soft news includes issues related to the social sphere which women are more familiar with, such as education, health care, lifestyle and human interest.